Whatsapp Based Learning In The Midst Of Covid-19 Pandemic: A Field Study In Mi Shibyanul Islamiyah Jember - Maghhfirah, Naily (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2023)
This study aims at analyzing WhatsApp based learning on the achievement and learning difficulties of elementary school students. The method used in this research was descriptive qualitative with a case study approach. The population of this research is elementary schools of MI Shibyanul Islamiyah on Jl. Gurami no.60 Dukuhmencek Sukorambi Jember. Through purposive sampling technique from several informants. Informants consist of headmaster, teachers, parents of students, and students. Data collection in this study was carried out by: (1) interviews; (2) observation; and (3) documentation. The data collected through interviews, observation and documentation were then analyzed using inductive descriptive techniques. Data analysis was performed by data reduction data display, and conclusion. The results of the research of the three respondents agreed with WhatsApp-based learning. It’s WhatsApp-based learning an application there are obstacles experienced by teachers, parents and students, including the lack of facilities, and students bored the learning process.